PENGARUH LIKUIDITAS DAN AKTIVITAS TERHADAP PROFITABILITAS PADA PT. INDOSAT, TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007-2014 - Apit Yuliman Ermaya; Muhammad Iqbal; Febby Cameliana Putri (Fakultas Ekonomi UNIBBA, 2016)
This research was conducted at PT. Indosat, Tbk. The purpose of this study was to determine the effect of liquidity and activity on profitability at PT. Indosat, Tbk, based on initial observations there is a phenomenon that has increased profitability for 8 (eight) period and this is thought to be caused by fluctuations in liquidity and activity factors. The method used is descriptive method with quantitative approach. The population used in this study is the annual financial statements of PT. Indosat, Tbk. whereas samples taken are the financial statements. Indosat, Tbk. from 2007 until 2014 or as much as 8 (eight) years. The sample selection using purposive sampling method. The data used is secondary data. Statistical methods used in this research is the analysis of multiple linear regression and multiple correlation analysis using IBM SPSS 20 version 20 program and count manually using the formula. The results showed that the partial correlation between liquidity with profitability relationships moderate and negative, as shown by the correlation of -0,481 and t-test results indicate that the effect is not significant that the t-count is smaller than t-table as well as the probability more greater than 0,05, then Ho accepted and Ha rejected. Partial correlation between the activity with very strong profitability and negative, as indicated by the correlation of -0,835 and t-test results showed that the significant influence that the ttest bigger than t-table, and the probability is less than 0,05, then Ho is rejected and Ha accepted. Simultaneous correlation between liquidity and profitability of activity with a very strong and positive, as indicated by the correlation of 0,852 and f-test results show that a significant impact is f-count is greater than f-tables as well as the probability is less than 0,05, then Ho rejected and Ha accepted. This influence is shown also by the coefficient of determination of 72,6% and the remainder are other factors that also influence but not examined by 27,4%. The conclusion that the liquidity and activity made a positive contribution to profitability in PT. Indosat,, Tbk